Research landscape and emerging trends of diabetes-associated cognitive dysfunction: a bibliometric analysis - He, Siyi; Liang, Qingchun; Zhu, Jie; Wang, Chen; Lin, Xiafei; Wu, Duozhi; Zhang, Wenqi; Lin, Guanwen; Wang, Zhihua (Frontiers in Neuroscience, 2023)
Background Diabetes-associated cognitive dysfunction (DACD) is a common and serious complication in diabetes and has a high impact on the lives of both individuals and society. Although a number of research has focused on DACD in the past two decades, there is no a study to systematically display the knowledge structure and development of the field. Thus, the present study aimed to show the landscape and identify the emerging trends of DACD research for assisting researchers or clinicians in grasping the knowledge domain faster and easier and focusing on the emerging trends in the field. Methods We searched the Web of Science database for all DACD-related studies between 2000 and 2022. Bibliometric analysis was conducted using the VOSviewer, CiteSpace, Histcite, and R bibliometric package, revealing the most prominent research, countries, institutions, authors, journals, co-cited references, and keywords. Results A total of 4,378 records were selected for analysis. We found that the volume of literature on DACD has increased over the years. In terms of the number of publications, the USA ranked first. The most productive institutions were the University of Washington and the University of Pittsburgh. Furthermore, Biessels GJ was the most productive author. Journal of Alzheimers Disease, Diabetes Care, and Frontiers in Aging Neuroscience had the most publications in this field. The keywords“dementia,” “alzheimers-disease,” “cognitive impairment” and “diabetes” are the main keywords. The burst keywords in recent years mainly included “signaling pathway” and “cognitive deficit.” Conclusion This study systematically illustrated advances in DACD over the last 23 years. Current findings suggest that exploring potential mechanisms of DACD and the effect of anti-diabetes drugs on DACD are the hotspots in this field. Future research will also focus on the development of targeted drugs that act on the DACD signaling pathway.